Influence “N” Notation on Stock Price: Study in Multiple Voting Shares - Kurniasih, Ninik; Irawati, Rika; Haryati, Haryati (Newinera Publisher, 2024)
Multiple Voting Share (MVS) is classification of shares in which every single one share can prodive more than one vote to shareholders eligible. The revocation was indicated in the regulation of Indonesian Otoritas Jasa Keuangan (POJK) number 22/POJK.04/2021 about implementing the classification of share voting right multiple or multiple voting share who released officially by December 2021. This similar line with the regulation of BEI (Indonesian Stock Exchange) then released. There is special notation, specially N notation, its given to issuers that has recorded on market exchange. Multiple voting share is identified as total asset and free float ratio as well. This study attempts to testing whether N notation (total asset and free float ratio) are impacted on stock price on multiple voting share.The benefits on this research is giving the investors informations about the notation, that they have to be careful, and avoid significant risk, This research is an explanatory method, backed by secondary data using. The technique of analysis is statistic testing classic assumption as normalty, multicolinierity, autocorrelation and heteroskedasticity to full fill the regression in completely. The Result found that 0,077 of total asset in partial is no effect on the stock price, While the 0,127 of free float ratio in partial is no effect on the stock price too. The score of these independent variables is above the alpa five percent, so both total asset dan free float ratio none that influence to the stock price.